PELATIHAN PUBLIC SPEAKING UNTUK MENINGKATKAN KETERAMPILAN PSIKOMOTOR SISWA SMK 6 SEMPAJA - Deandlles Christover; Paren Maicatrine (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2023)
Public speaking or speaking in public is the most feared thing by most high school students. This fear is caused by a lack of interest in reading, lack of confidence, fear of being wrong, having bad experiences when doing public speaking and weak mentality, and excessive feelings of anxiety. Public speaking activities are not commonly done by high school/vocational high schools students, such as class presentations and group discussions. However, in delivering class presentations students do not yet have the skills to convey messages properly, because it is important for high school students to know how to speak in public to help convey messages properly, clearly, and precisely, and to prepare themselves for higher education, the environmental community and work environment. Therefore, the purpose of this PKM is to provide knowledge about the importance of public speaking, public speaking skills, improve public speaking skills, and public speaking training as a form of improving students' psychomotor skills. The methods that will be carried out in this PKM activity are seminars, practice, and students will be given modules as learning materials to improve their psychomotor skills. Community service in the form of public speaking skills training is important to be learned early on by high school / vocational students so that when presenting in front of the class they are more confident and can convey messages well as well as train themselves and prepare themselves for college and the world of work. The target of this community service activity is grade 12 students at SMK 6 Sempaja, Samarinda City, East Kalimantan. The output of this Community Service activity is published in national journals.